GAMBARAN TINGKAT PENGETAHUAN CARA PENGGUNAAN (CONTROLLERMETERED DOSE) INHALER SEBAGAI TERAPI ASMA PADA MASYARAKAT DI KELURAHAN PATRANG JEMBER - N, Isnawati.; Mayasari. S; Wardatul. A (Bajang Institute, 2024)
Asthma is a chronic inflammatory disease of the airway that is characterized by episodic wheezing, coughing, and tightness in the chest caused by blockage in the airway. Asthma treatment requires long-term medication. One of the drugs used during an asthma attack is MDI or Metered Dose Inhalation which is a drug using a metered dose that requires certain inhalation techniques so that the dose of the drug can reach the respiratory tract. The class of drugs packaged in the form of MDI is divided into several groups, namely inhaled steroids (fluticasone propionate, budeneside), beta-2 agonists (salmeterol, salbutamol, terbutaline, prokaterol), a combination of steroids and beta-2 agonists (fluticasone and salmeterol), anticholinergics, and methylsanthin (ipratropium bromide) (Depkes RI, 2008). The purpose of this study was to determine the accuracy of the use of controllermetered-dose inhalers in asthma patients in the Patrang village area. The method used in this study was observational with a cross sectional design by analyzing the knowledge of asthma patients when using Controlledmetered-Dose Inhaler (MDI) preparations in the Patrang Jember Region in 2023. The research variable studied was an explanation of the technique of how to use Controlledmetered-Dose Inhaler (MDI) by asthma patients when an asthma attack occurs. The results of the study obtained the first critical step stage 100%, the second stage 93% and the third stage 100%. The results of the use category included in the category of optimal techniques as much as 40%, adequate techniques 57% and less techniques as much as 3%.